COMPARATIVE ANALYSIS OF VARIOUS METHODS OF GUM RETRACTION IN ORTHOPEDIC DENTISTRY - Egamov Sheroz Anvarovich, Burxonova Zarafruz Qobilovna (Journals Park Publishing, 2023)
In modern orthopedic dentistry, the display of the features of the formed stump of the prepared tooth, in particular, the ledge line, is a necessary condition for high-quality restoration. We performed gum retraction in 40 patients aged 21 to 53 years, using traditional and modern methods. Retraction threads were used, the impregnation of which includes various chemical compounds, as well as pastes for gum retraction. The results are considered from the point of view of the physicochemical properties of the means used, the quality of the impressions obtained, the atraumaticity during retraction and the effect on the general somatic state of the patient’s body. The results were recorded using a multifunctional laser diagnostic complex “LAKK-M” and an electronic tonometer. The quality of the impressions was assessed visually. We made conclusions about the advantages and disadvantages of the systems used, their impact on the general dental status of patients.
Keywords: effect of gingival retraction, retraction threads, retraction pastes, impressions in orthopedic dentistry, epinephrine.